INDIGENOUS MILITARIZATION IN THE CAPITANIA OF PERNAMBUCO IN THE CENTURY XVII: SHRIMP, THE HISTORY OF A TITLE. - Juliana Elias (Clio: Revista de Pesquisa Histórica, 2007)
This work deals with the lineage of the Shrimp Indian, which acquired importance from the need for protection of the Colony, considering that the Crown did not intend to bear the costs of maintaining a troop parked in colonial territory. Thus, the solution was to create a local militia, led by Camarão, who, little by little, gained the trust of Portugal, giving his troops a prominence until then denied to a peripheral social group. In this sense, the relevance achieved by Filipe Camarão and his descendants shows another face of Brazilian history, placing these peoples with a power of action that actively interfered in the plans and projects idealized by the Crown for the Colony.